Cardiovascular magnetization transfer ratio imaging compared with histology: A postmortem study. Issue 4 (October 2014) - Crooijmans, Hendrikus J.A.; Ruder, Thomas D.; Zech, Wolf‐Dieter; Somaini, Sandra; Scheffler, Klaus; Thali, Michael J.; Bieri, Oliver
<x xml:space="preserve">Abstract</x> Cardiovascular magnetization transfer ratio (MTR) imaging by steady state free precession is a promising imaging method to assess microstructural changes within the myocardium. Hence, MTR imaging was correlated to histological analysis. Three postmortem cases were selected based on a suspicion of myocardial infarction. MTR and T2‐weighted (T2w) imaging was performed, followed by autopsy and histological analysis. All tissue abnormalities, identified by autopsy or histology, were retrospectively selected on visually matched MTR and T2w images, and corresponding MTR values compared with normal appearing tissue. Regions of elevated MTR (up to approximately 20%, as compared to normal tissue), appearing hypo‐intense in T2w‐images, revealed the presence of fibrous tissue in microscopic histological analysis. Macroscopic observation (autopsy) described scar tissue only in one case. Regions of reduced MTR (up to approximately 20%) corresponded either to (i) the presence of edema, appearing hyperintense in T2w‐images and confirmed by autopsy, or to (ii) inflammatory granulocyte infiltration at a microscopic level, appearing as hypo‐intense T2w‐signal, but not observed by autopsy. Findings from cardiovascular MTR imaging corresponded to histology results. In contrast to T2w‐imaging, MTR imaging discriminated between normal myocardium, scar tissue and regions of acute myocardial infarction in all three cases. J. Magn. Reson. Imaging 2014;40:915–919. © 2013 Wiley Periodicals, Inc.